2020
DOI: 10.3390/polym12040863
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Properties of Transparent Bamboo Prepared by Epoxy Resin Impregnation

Abstract: In this paper, Moso bamboo (Phyllostachys heterocycle) before and after heat treatment were used as raw materials to prepare transparent bamboo (TB). In an acidic environment, the lignin contained in the bamboo material was removed to obtain a bamboo template, and an epoxy resin similar to the cellulose refractive index was used for vacuum impregnation into the bamboo template to obtain a transparent bamboo material. The purpose of this study was to compare the physical and chemical properties of TB and origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…However, once the delignification has been accomplished, various options exist for the polymer impregnated wood, as well reviewed by [59,60]. Polymethyl methacrylate is a commonly chosen polymer for this [57], although other researchers have considered epoxy resins, PVA or other systems [58,59,[61][62][63][64]. In order to make a two-component material (such as composite or impregnated wood) transparent, the difference between the refracted indices of the two phases must be minimised to reduce diffraction at interfaces between the two phases [57].…”
Section: Delignification Combined With Polymer Impregnation-transparent Woodmentioning
confidence: 99%
“…However, once the delignification has been accomplished, various options exist for the polymer impregnated wood, as well reviewed by [59,60]. Polymethyl methacrylate is a commonly chosen polymer for this [57], although other researchers have considered epoxy resins, PVA or other systems [58,59,[61][62][63][64]. In order to make a two-component material (such as composite or impregnated wood) transparent, the difference between the refracted indices of the two phases must be minimised to reduce diffraction at interfaces between the two phases [57].…”
Section: Delignification Combined With Polymer Impregnation-transparent Woodmentioning
confidence: 99%
“…Compared with natural bamboo, the tensile strength shows an increment from 69 to 162 MPa, and the toughness is also improved. Wu et al [164] found that the difference between the inner and outer walls of bamboo, as well as the heat treatment, shows a great influence on the performance of the delignified bamboo/epoxy composite. By cross-linking delignified bamboo with boric acid treatment, the obtained composites exhibit ∼2 times increments of tensile strength, modulus, and impact strength [165].…”
Section: Continuous Phase Enhancement Strategymentioning
confidence: 99%
“…At present, in order to avoid the defects caused by the natural shape of bamboo, there have been developments of bamboo-based composite materials using industrialized production processes, including, for example, bamboo plywood, laminated bamboo lumber, and bamboo scrimber. They are widely used in furniture, flooring, construction, civil engineering, and other fields [ 8 , 9 , 10 ]. However, due to the absence of transverse ray cells in bamboo tissues and the unobvious flow, wetting, and penetration depth of the liquid adhesive on the surface of the bamboo, the crosslinking of the adhesive and the bamboo material is unable to achieve the mechanical coupling effect with the wood [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%